Pengaruh Motivasi, Displin Kerja Dan Komunikasi Terhadap Kinerja (Studi pada Pengurus Forum Komunikasi Mahasiswa Sumenep (FKMS) Joko Tole UNISMA) - Ach Zainur Ridha; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to analyze the effect of motivation, work discipline and communication on the performance of the management of FKMS Joko Tole UNISMA. The variables used in this study are performance variables (dependent variable), while the independent variables are motivation, work discipline and communication. The results of the study partially concluded that the motivation variable had an effect on performance, work discipline had an effect on performance and communication had an effect on performance. Keywords: Motivation, Work Discipline, Communication, Performance